Criteria for Employability in Professional Technical Education. Tensions and Challenges in Health Specialty, Araucanía, Chile - Riquelme-Brevis, Hernán (2018)
The present research analyzes the employability criteria, when hiring the services of nursery graduates from three secondary technical schools in La Araucanía, Chile. This research project used a mixed methodology, so it was possible to contact health employees from public and private areas, such as teachers, graduates and students from three secondary technical schools and apply to them various research techniques such as questionnaires, in-depth interviews, and focus groups. Among the main results, it is worth mentioning: the re-articulation experienced by the technical and professional high schools in Chile, related to civil society and health system; the need to reinforce the dialog among institutions in the health and sanitary system; technical training and development of socio-emotional abilities of students and research graduates, and finally the demand to advance towards social validity of professional technicians in the health area. Finally, this research aims to contribute to finding mechanisms to improve the work performance of health technicians, as well as identifying obstacles that impede the development of secondary technical education in the country.